A Study on the Usage of the Words ana ~ ene and apa ~ aba Denoting in Kazakh and Their Usein Historical and Modern Turkic Dialects - Serdar Özdemir (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Kinship terms in Kazakh are a significant elements reflecting the family structure and society's values. These terms include rich vocabulary that describes an extended family structure. Kinship terms are also a crucial part of cultural identity and serve as milestones demonstrating the historical significance of family structure. Commonly used kinship terms for both women and men in Kazakh words like 'ata, ana, äke, ağa, ini, and apa.' Among these, those used to express the closest family relationships, especially the concept of 'mother,' stands out. Some examples include 'ana, ene, şeşe, apa, aba, ӓni, mama, and ӓje.’ This study examines the terms representing the concept of 'mother' in Kazakh, focusing on the expressions 'ana ~ ene' and 'apa ~ aba' within the context of historical and modern Turkic dialects. While 'ana' is more commonly used in Kazakh, the form 'ene' is preferred in some regions. Similarly, the words 'apa' and 'aba,' which also mean 'mother,' show regional variations in their usage. Such words have evolved throughout Turkic people’s historical development and linguistic evolution. These terms in Kazakh are not just words but also reflect the social structure of Kazakh society and the value placed on family relationships.